Case report: Malignant priapism: penile metastasis from prostate cancer with low serum PSA level - Zhang, Zhiqiang; Xu, Mengfan; Shang, Muhan; Liu, Zhiqi; Yang, Lei; Yu, Dexin (Frontiers in Oncology, 2025)
BackgroundPenile metastasis originating from prostate cancer is an extremely rare condition, typically associated with a poor prognosis. Therapeutic approaches are not well established and may require individualized adaptation based on clinical assessment. Radiotherapy is commonly utilized to alleviate symptoms. For patients presenting with priapism, palliative penectomy is often recommended.Case presentationThis report describes a case of penile metastasis from prostate cancer in a 74-year-old man who presented with priapism. Positron emission tomography/computed tomography (PET/CT) imaging identified metastases in the penis, along with multiple metastatic sites in the lungs, left iliac vascular lymph nodes, abdominal and pelvic lymph nodes, and bones. A palliative penectomy was performed to relieve symptoms, and postoperative pathology confirmed the presence of penile metastasis originating from prostate cancer. Following the penectomy, the patient received ongoing androgen deprivation therapy (ADT) along with androgen receptor antagonists (enzalutamide).ConclusionsPenile metastasis from prostate cancer is a rare condition and is often initially misdiagnosed due to the presentation of occult malignancy. This case highlights the need for clinicians to enhance their understanding and diagnostic accuracy regarding penile metastases. Imaging techniques such as Fluorine-18-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) and Gallium-68 prostate-specific membrane antigen positron emission tomography/computed tomography (Ga-68 PSMA PET/CT) can detect prostate cancer lesions even at low serum prostate-specific antigen (PSA) levels, thereby improving diagnostic precision for prostate cancer.